The effect of a maternal history of childhood abuse on adrenocortical attunement in mothers and their toddlers - Fuchs, Anna; Möhler, Eva; Resch, Franz; Kaess, Michael (Developmental psychobiology, 2017)
We investigated circadian mother-child adrenocortical attunement in the context of a maternal history of childhood abuse (HoA). Mothers were screened after birth using the Childhood Trauma Questionnaire. Women reporting moderate or severe abuse formed the HoA group (n = 37; HoAG) and were compared with a non-maltreated comparison group (n = 45; CG). Three years later, cortisol awakening response (CAR) and diurnal slope (DSL) were assessed. Mother-child interaction was coded using the Emotional Availability Scales at 12 months of age. For the CAR, we found adrenocortical attunement only in the HoAG (2-way interaction: p = .004), particularly if mothers scored low on structuring (3-way interaction: p = .042) and children scored low on responsiveness (3-way interaction: p = .044). DSL-attunement was dependent on maternal sensitivity (3-way interaction: p = .012) and child involvement (3-way interaction: p = .012). In the context of a maternal HoA, it seems possible for mother-child-dyads to show less optimal interactional quality but be stronger attuned to each other biologically.